Rule learning enhances structural plasticity of long-range axons in frontal cortex - Carolyn M. Johnson (Nature Portfolio, 2016)
The orbitofrontal cortex is associated with foraging behaviour yet the structural changes underlying such rule-based learning remain unclear. Here, the authors imaged OFC axons throughout a digging-based odour discrimination task and found correlations between the rate of bouton turnover and the behavioural strategies of individual mice.